الادارة الرقمية بين الواقع والتطبيق (دراسة ميدانية على كلية التقنية الهندسية صرمان) (Comprehensive Journal of Science, 2025)
study at the College of Engineering Technology, Sorman. The study used the descriptive analytical approach to present the problem, and used a questionnaire as a tool for collecting data. The study community consisted of managers, heads, and employees of departments at the College of Engineering Technology, Sorman, numbering about (86) individuals. The number of questionnaires entered for analysis amounted to (47) questionnaires. The study used the intentional sampling method, in addition to adopting the analytical statistical method to analyze the questionnaire through the Statistical Package for the Social Sciences (SPSS) program. The study reached the following results: The reality of applying digital management to its requirements is the support of senior management, the availability of organizational procedures. Availability of networks and communications, availability of devices and equipment, availability of software , and the availability of human cadres in the college to implement digital management). indicates the presence of its application in the college to a medium degree because the arithmetic mean equals (3.204) and a relative weight of (55.11%).
Keywords: Digital Management